Model zaopatrzenia w controllingu logistycznym przedsiębiorstwa handlowego - Skoczylas, Krystyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In the paper the factors, which have influence on the supply process are described. The models of the optimal supply are presented. The proposal of the new model based on the return rate is described. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 387-393